Demographic responses to the manipulation of adult females in corn mouse populations - Gomez, Maria Daniel (2012)
Variation in population abundance is a consequence of changes in demographic parameters such as survival and recruitment. These demographic parameters can be affected by intraspecifi c competition, thus adults may play an important role influencing the survival and/or reproduction of juvenile individuals in many species of small mammals. We present an analysis of Calomys musculinus populations using capturemark- recapture models in order to evaluate the effect of female removal on their demography. The study was carried out in four enclosures during two different periods: a reference period and a treatment period, with the removal of adult females. Reference period was analyzed to describe population demography without manipulations. In treatment period, two control enclosures maintained both parents remained with their offspring whereas other two enclosures had their adult females removed. Seven monthly trapping sessions were carried out (spring to autumn). We estimated apparent survival, recruitment, population growth rates and recapture probabilities. Models considered these parameters constrained to vary as a function of time, enclosure, sex and/or treatment. During the reference period survival and recruitment showed sex and time effects, survival was higher in females and decreased towards June; recruitment showed a peak in February with a higher number of recruited males; population growth rates peaked in February and decreased towards June. During the treatment period survival showed time effect whereas recruitment showed time and treatment effects. Survival was higher at the beginning of the breeding period and decreased afterwards, and recruitment was higher in control enclosures; population growth rates showed a similar pattern than in reference period. There were not differences in growth rates and abundances between control and experimental enclosures. Under our experimental and methodological conditions, the results would indicate that the absence of females in experimental enclosures was not enough to cause a clear impact on final population size.